2020
DOI: 10.3390/cancers12061619
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation and Activation of Haemostasis Predict Poor Prognosis and Response to Chemotherapy in Patients with Advanced Lung Cancer

Abstract: Systemic inflammation and activation of haemostasis are common in patients with lung cancer. Both conditions support tumour growth and metastasis. Therefore, inflammatory and haemostatic biomarkers might be useful for prediction of survival and therapy response. Patients with unresectable/metastatic lung cancer initiating 1st-line chemotherapy (n = 277, 83% non-small cell lung cancer) were followed in a prospective observational cohort study. A comprehensive panel of haemostatic biomarkers (D-dimer, prothrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
1
21
0
6
Order By: Relevance
“…The detection methods used in the studies include immunoturbidimetry assay [ 15 27 ], latex assay [ 1 , 28 30 ], and enzyme-linked immunosorbent assay (ELISA) [ 9 , 31 – 36 ]. Since different detection methods may affect the level of D-dimer, we conducted a subgroup analysis to further analyze the impact of different detection methods on the prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The detection methods used in the studies include immunoturbidimetry assay [ 15 27 ], latex assay [ 1 , 28 30 ], and enzyme-linked immunosorbent assay (ELISA) [ 9 , 31 – 36 ]. Since different detection methods may affect the level of D-dimer, we conducted a subgroup analysis to further analyze the impact of different detection methods on the prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma D-dimer is a small cross-linked protein generated from fibrin degradation and is an essential indicator of coagulation dysfunction (2,(9)(10)(11). It has critical implications for the exclusion of cancer-related thrombosis clinically (12).…”
Section: Introductionmentioning
confidence: 99%
“…He et al considered that the imaging biomarkers extracted by tumor mutational burden could effectively predict the therapeutic effect of immune checkpoint inhibitors in advanced NSCLC patients [ 59 ]. Moik et al demonstrated that inflammation and hemostasis could serve as biomarkers for unfavorable prognosis and poor therapy response in advanced lung cancer patients [ 60 ]. Perrone et al found that hypercholesterolemia implies a low-grade inflammatory state that could distinguish the best beneficiaries of immunotherapy in NSCLC [ 61 ].…”
Section: Discussionmentioning
confidence: 99%